Severidade da pinta preta em genótipos de tomateiro cereja e avaliação de fungicidas e produtos alternativos no crescimento micelial e germinação de Alternaria tomatophila - Hugo Cesar Rodrigues Moreira Catão (2011)
Among the fungal diseases that affect tomato, the black spot, caused by the fungus Alternaria tomatophila, is one of the most important of the crop. The use of resistant varieties and products that can induce resistance emerge as an option of low cost and less damage to the environment when compared to the use of agrochemicals. Thus, our objective with this research was to evaluate the severity of cherry tomato genotypes, the Alternaria tomatophila, in field conditions; determine the production of cherry tomato genotypes, by the number of bunches, number of fruits and number of fruits with black spot incidence and evaluate the in vitro effect of different products (cymoxail + mancozeb, potassium phosphite, copper oxychloride and biofertilizer) in mycelial growth and conidial germination of A. tomatophila. The genotype tomato cherry CH 152 presented resistance to pathogen Alternaria tomatophila. This same genotype and the Cherry Red were the most productive in relation to others, presenting a greater number of fruits per plant. In the CH 152 genotype were not observed fruits with incidence of Alternaria tomatophila. The weather conditions favored the establishment of the disease, providing increases in the severity. The fungicide cymoxanyl + mancozeb and the potassium phosphite 0-28-26 were more effective in inhibiting the mycelial growth and of the conidial germination of Alternaria tomatophila.